Intimate, ambivalent and erotic mentoring: Popular culture and mentor–mentee relational processes in Mad Men. (June 2014) - Buzzanell, Patrice M; D'Enbeau, Suzy
Mentoring centers on the development of another person through career, psychosocial and role modeling support. As popular cultural portrayals and gendered critiques of mentoring show, not all can be categorized as rational, instrumental and positive. There often are unconscious forces that drive particular mentoring arrangements and offer entrée points into mentorship analyses that contrast with rational approaches. Popular culture images provide an arena to critique dominant mentoring practices. Towards this end, we critically examine the award-winning drama Mad Men (Weiner, 2007) and uncover how non-rational mentoring practices are depicted. We argue that characters engage in intimate, ambivalent and erotic mentoring processes in which loyalties shift and neuroses reflect the nature of workplace social relations. Our critique displays characters' complicity in perpetuating asymmetrical gendered workplace relations through practices that are seemingly non-rational, presumably meritocratic and/or captured by archetypal mentoring relationships.